Water and Soil Accelerator Co-Creation Workshop: summary report - Chinembiri, Evans; Jacobs-Mata, Inga (International Water Management Institute, 2025)
The Water and Soil Accelerator Co-Creation Workshop Summary Report documents the outcomes of a two-day multi-stakeholder workshop held on October 8–9, 2024 in Lusaka, Zambia, convened by the International Water Management Institute (IWMI) with support from the United States Government. The workshop formed a key milestone in the design of the Water and Soil Accelerator, a three-year initiative aimed at strengthening climate-resilient, rainfed agricultural systems in Zambia and Malawi. Participants from government, research institutions, NGOs, private sector actors, financial services, and farmer organizations collaboratively identified priority challenges, scalable interventions, and partnership models to improve sustainable water and soil management. Key thematic focus areas included sustainable water management, green infrastructure, soil health and agronomy, climate information services, collective natural resource governance, financing and enabling environment, and gender equality and social inclusion. Field visits and breakout discussions highlighted proven practices such as agroforestry, conservation agriculture, watershed-level water management, and inclusive climate advisory services. The workshop concluded with agreement on coordination mechanisms, partner roles, and next steps, including a competitive call for proposals, the establishment of regional coordination platforms, and the development of a robust monitoring and evaluation framework to support rapid scaling and measurable impact.